Myxomycetes of the Monte Alto Protected Zone in Costa Rica: a case study - Rojas Alvarado, Carlos Alonso (2023)
A survey of myxomycetes was carried out during 2022 in the Monte Alto Protected Zone in Guanacaste, Costa Rica. Eighty samples of ground litter were collected from the premises around the headquaters and studied with the moist chamber technique. The resulting dataset was compared with an equivalent set from the Caribbean side of the country obtained in the same forest type in order to evaluate the previous observation that forests on the Pacific slope of Costa Rica seem to be associated with higher values of alpha diversity, when surveys are based on sporocaps and morphospecies. Results supported such observation to a degree, but also showed that the overlap among species assemblages within the same forest type could be affected by a different history of forest management. In the case of the Monte Alto Protected Zone, the observed diversity of myxomycetes suggested that the forests of this area have responded succesfully to the reforestation processes that took place more than 30 years ago.